Topical therapy with clobetasol propionate 0.025% for various dermatological conditions - Raj, Vishwanath Prem; Tayade, Nitin Pandit; Kiswe, Chandrashekhar V.; Shah, Nimesh Surendrakumar; Sengar, Suneel Singh; Pavan, Indira; Gamit, Sanjay Ramanbhai; Bansal, Mohit; Kumar, Sachin; Yadav, Ankit (International Journal of Research in Medical Sciences, 2022)
Topical corticosteroids (TC) are the most commonly prescribed medications for the treatment of several dermatoses. Owing to their potent effect of relieving symptoms, these drugs are indicated for the use of inflammatory and pruritic presentations of dermatologic conditions. Clobetasol propionate (CP) is the most common TC used to treat itching, redness, and swelling caused by some skin conditions. It possesses anti-inflammatory, antipruritic, and vasoconstrictive properties. To exert its effect, CP binds to cytoplasmic glucocorticoid receptors and subsequently activates glucocorticoid receptor-mediated gene expression, thus resulting in the synthesis of certain anti-inflammatory proteins, while inhibiting the synthesis of certain inflammatory mediators. This case series discusses the efficacy, safety, and clinical experience of using CP 0.025% cream for the treatment of different dermatologic conditions.